Assessing Option Grid® practicability and feasibility for facilitating shared decision making: An exploratory study. Issue 7 (July 2015) - Tsulukidze, Maka; Grande, Stuart W.; Gionfriddo, Michael R.
Highlights We assessed Option Grid® practicability and feasibility on shared decision making. In simulated consultations clinicians received high scores on information sharing. Preference elicitation and integration were not performed at an optimal level. Use of Option Grids® did not facilitate optimal levels of SDM competency.